Alteration of the Reproductive Indicators by the Presence of Leptospira spp. in Sows of Swine Farms - Ospina-Pinto, Maria Catalina; Rincón-Pardo, Manuel; Soler-Tovar, Diego; Hernández-Rodríguez, Patrícia (Acta Scientiae Veterinariae, 2019)
Background: Leptospirosis is a worldwide disease that impacts health, welfare and animal production. Manifestations in swine range from subclinical to severe cases of reproductive failure, generating abortions, embryonic resorption, litters with few piglets, and piglets born weak or dead, which causes great economic losses. Tropical conditions in Colombia favor transmission and maintenance of Leptospira, highlighting the importance of implementing direct diagnostic techniques such as isolation through culture to reach a definitive diagnosis. The objective of the present study was to relate reproductive indicators behavior with the presence of Leptospira spp. in two pig farms in Cundinamarca, Colombia. Materials, Methods & Results: Sows in reproductive stage in two pig farms were selected. A clinical examination of the animals was performed to demonstrate the presence of signs suggestive of Leptospirosis, also the sow records were reviewed to find reports of any of these clinical manifestations, and the average of the reproductive indicators was calculated to set which were altered in the sows. Blood and urine samples were obtained and analyzed by microscopic agglutination test (MAT) and isolation through culture, respectively. Among the altered reproductive indicators were identified: total pigs born (TPB) in 72.5%, stillbirths (SB) by 70%, mummified pigs (MUM) in a 52.5%, pre-weaning death (PWD) by 40% and the 24 h mortality (M24h) in the 20%. The 77.5% of the sows were positive by MAT. The predominant serovars of Leptospira spp. included Grippotyphosa (67.5%), Canicola (22.5%), Icterohaemorrhagiae (20%), Hardjo (17.5%) and Pomona (12.5%). The bacterium was isolated in 32.5% of the analyzed urine samples. There is increased risk of alteration in the indicators M24h (1.27), TPB (1.08), SB (1.15) and MUM (1.27) with the presence of Leptospira by isolation through culture. Discussion: The birth of weak piglets and the alteration of indicators such as SB were the most common findings in this study, which are of the major alterations caused by the bacteria because Leptospira can be located in the uterus. Positive cultures, 32.5% (13/40), indicate a high percentage of positive animals in the population. The total of positive culture results reveal that humans, pigs and other animal species from the farms and surrounding areas, are at risk of exposure to the bacteria, because these positive sows are eliminating the microorganism through urine to the environment, representing a problem for public health. This is why it is important to perform the identification of bacteria in urine. It establishes whether the animal is a carrier, although the non-detection of the microorganism in the urine does not rule out that this is a chronic renal carrier because it may indicate that at the moment of the test the animal was not excreting detectable amounts of the bacteria. The total of positive sera (77.5%) indicates a high seropositivity of swine leptospirosis in the population. Regarding serovars of Leptospira spp. identified, Grippotyphosa has the largest presentation (67.5%), therefore, as pigs are not maintenance hosts of this serovar, the results of this study suggest that synanthropic rodents that are found on farms may be transmitting the bacteria to pigs. The reproductive indicators related to the Leptospira serovars by X2 test, demonstrated significant association between the average of SB and the serovar Pomona, which has as reservoir the swine species and it is related with the production of piglets born dead, while through the Pearson correlation coefficient it was found that the greater the number of positive samples to serovar Pomona there is a greater presentation of weak piglets, and also was demonstrated that animals with Leptospira spp. have a higher risk to present alterations of the M24h, the average of TPB, SB and MUM.